Media CD Interactif Understanding The Level of Student Teaching In Eye Anatomy And Physiology - Muhamad Syamsul Arif Setyo Negoro; Purnomo Purnomo; Sugih Wijayanti (Jurnal LINK, 2014)
This study is to determine the effect of the use of interactive CD media to the level of understanding of teaching anatomy and physiology of eye. This is a quasi experiment research with pre and post test control grouph design. The number of samples in this study is 79 people. The data were processed with t-test to determine the differences in physiological anatomy score between groups before treatment, the difference in the value between groups after treatment, the difference in value before and after treatment in both groups and the difference in the average increase in the value of physiological anatomy after the treatment between groups. The results of the t test for differences in anatomy physiology score before the treatment between groups (p=0.53), the difference in value between groups after treatment (p=0:03),the difference in value before and after treatment in both groups (p=0.00) and the average difference in the increase in value physiological anatomy after the treatment between groups (p=0.023 ). In conclusion, the treatment group had a greater understanding of the level compared with the control group.